Fans of Violent Music: The Role of Passion in Positive and Negative Emotional Experience. (June 2022) - Olsen, Kirk N.; Powell, Merrick; Anic, Aydin; Vallerand, Robert J.; Thompson, William Forde
Extreme metal and rap music with violent themes are sometimes blamed for eliciting antisocial behaviours, but growing evidence suggests that music with violent themes can have positive emotional, cognitive, and social consequences for fans. We addressed this apparent paradox by comparing how fans of violent and non-violent music respond emotionally to music. We also characterised the psychosocial functions of music for fans of violent and non-violent music, and their passion for music. Fans of violent extreme metal ( n =46), violent rap ( n =49), and non-violent classical music ( n =50) responded to questionnaires evaluating the cognitive (self-reflection, self-regulation) and social (social bonding) functions of their preferred music and the nature of their passion for it. They then listened to four one-minute excerpts of music and rated ten emotional descriptors for each excerpt. The top five emotions reported by the three groups of fans were positive, with empowerment and joy the emotions rated highest. However, compared with classical music fans, fans of violent music assigned significantly lower ratings to positive emotions and higher ratings to negative emotions. Fans of violent music also utilised their preferred music for positive psychosocial functions to a similar or sometimes greater extent than classical fans. Harmonious passion for music predicted positive emotional outcomes for all three groups of fans, whereas obsessive passion predicted negative emotional outcomes. Those high in harmonious passion also tended to use music for cognitive and social functions. We propose that fans of violent music use their preferred music to induce an equal balance of positive and negative emotions.